1998
DOI: 10.1109/36.718640
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory measurements of sea ice: connections to microwave remote sensing

Abstract: The connections between laboratory measurements and remote-sensing observations of sea ice are explored. The focus of this paper is on thin ice, which is more easily simulated in a laboratory environment. We summarize results of C-band scatterometer measurements and discuss how they may help in the interpretation of remote-sensing data. We compare the measurements with observations of thin ice from ERS and airborne radar data sets. We suggest that laboratory backscatter signatures should serve as bounds on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A similar depolarization was also observed over snow deposition, and this depolarization was explained by increases in volume scattering or increases in absorption by wet snow [Garrity, 1992;Wensnahan, 1995;Grenfell et al, 1998;Hwang et al, 2007]. Kwok et al [1998] also found that active microwave signatures were affected by seawater flooding the surface. Besides the direct contribution of ice temperature on T B , the ice temperature controls the brine volume in thin ice and thus also indirectly affects microwave emissivity.…”
Section: Introductionmentioning
confidence: 63%
“…A similar depolarization was also observed over snow deposition, and this depolarization was explained by increases in volume scattering or increases in absorption by wet snow [Garrity, 1992;Wensnahan, 1995;Grenfell et al, 1998;Hwang et al, 2007]. Kwok et al [1998] also found that active microwave signatures were affected by seawater flooding the surface. Besides the direct contribution of ice temperature on T B , the ice temperature controls the brine volume in thin ice and thus also indirectly affects microwave emissivity.…”
Section: Introductionmentioning
confidence: 63%
“…This variation in difference is likely due to the difference in polarization: RADARSAT has an HH polarization, and ERS-2 has a VV polarization. Laboratory measurements of radar backscatter from sea ice, the difference in HH and VV polarization, were greatest for bare ice and less for ice covered with frost (Kwok and others, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Air temperatures during the fieldwork and image acquisition averaged –3˚ to –4°C with a good wind. High sublimation rates are common in the valley, cooling and drying the surface significantly (Lewis and others, 1995). If the ice surface was wetter than the snow, the image should exhibit a broad transition zone between the ice and snow because the patchy snow and ice would present a mixture for the SAR pixels, changing in tone with the changing snow cover.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, backscatter from dry snow-covered ice was a slightly stronger scatter than flooded ice. An even larger damping of backscatter (4-8 dB decrease) was observed during the ARI [15] when a new ice surface was flooded with saline water. Wide-band radar data acquired during the ARI support these observations and suggest the crossover in dominant scattering mechanisms occurs between 9 and 10 GHz for new snow on new ice [3], [4].…”
Section: B Field Componentmentioning
confidence: 97%